EFEKTIVITAS NEURODYNAMIC EXERCISE DAN NEUROMUSCULER TAPING TERHADAP FUNGSI TANGAN PADA IBU HAMIL DENGAN CARPAL TUNNEL SYNDROME: STUDI KASUS - Ayu Permata; Muawanah, Siti; Rizal, Yose; Taqwin Alhabsyi, Ahsana (JURNAL PROFESIONAL FISIOTERAPI, 2026)
Introduction: Carpal Tunnel Syndrome (CTS) is a neuromusculoskeletal condition commonly experienced by pregnant women in the third trimester. This condition is caused by fluid retention, which causes swelling and compression of the nerve within the carpal tunnel. Hormonal fluctuations such as progesterone, estrogen, renin, and angiotensin during pregnancy contribute to swelling and compression of the median nerve. Symptoms resulting from median nerve compression include pain, numbness, and tingling sensations in the hand. These symptoms can reduce hand functional ability, interfere with daily activities, and decrease the quality of life of pregnant women. The management of CTS in pregnancy is limited in the use of innovative, safe, and effective non-pharmacological, physiotherapy-based interventions to address movement and hand function disorders. Neurodynamic exercise is a median nerve mobilization technique that alters nerve length in relation to surrounding structures and improves intraneural blood flow. This technique focuses on stretching methods that reduce neural tension and help restore nerve function. Neuromuscular taping (NMT) helps reduce fluid congestion, improve blood and lymphatic circulation, decrease excess heat, restore tissue homeostasis, and reduce inflammation and pain receptor hypersensitivity. Objective: To determine the effectiveness of neurodynamic exercise and neuromuscular taping as physiotherapy interventions on hand function in pregnant women with carpal tunnel syndrome. Methods: This study was a case study using a single-subject research design conducted on a third-trimester pregnant woman with CTS. The physiotherapy program was delivered six times over three weeks, from April 13 to April 29, 2025. Hand functional ability was evaluated using the Wrist–Hand Disability Index (WHDI). Results:After the physiotherapy intervention, the WHDI score decreased from 40% (moderate disability) before intervention to 18% (minimal disability) after intervention. Conclusion: Neurodynamic exercise combined with neuromuscular taping had a positive effect on hand functional ability in a pregnant woman with carpal tunnel syndrome.